Kitabiyyah Mother and Ḥaḍanah of the Muslim Child: Religious and Legal Practices in Pakistan - Salma Begum,; Mansoori, Muhammad Tahir (Journal of Islamic and Religious Studies, 2018)
The article attempts to analyze the religious and legal practices inside Pakistan regarding the issue of the kitabiyyah mother and ḥaḍanah of any Muslim child. The discussion primarily addresses the major issues emphasizing kitabiyyah mother and her relatives’ right to retain the custody of the Muslim child, and duration of ḥaḍanah under the supervision of kitabiyyah mother in shari‘ah and Pakistani Family Laws. Furthermore, it argues that kitabiyyah mother is permitted to raise the Muslim child according to her faith under both Islamic and Pakistani Family Laws. The article is delimited to the opinions of four Sunni schools of thoughts, Statute law, and Case laws. Nonetheless, in-depth comparative analysis has been carried out in most persuasive way to examine the rules related to kitabiyyah mother in custody of Muslim child after divorce under both Islamic Law, and Case Laws in Pakistan. Additionally, the existing similarities and differences consequent to religious differences have also been appropriately figured out to point out plausible way forward to address prevailing schism. Contradictions between the legal practices and Islamic law need keen attention Islamic and legal scholars to carefully craft to harmonize both in the best interest of child.